Technical Inefficiency of Manufacturing Industries In Malaysia - Alias, Radam; Shazali Abu, Mansor; Mansor, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2001)
The global recession from 1984-1986 has brought about significant structural changes to the Malaysian economy. The mid-1980s crisis revealed the stark reality that over-dependence on agricultural and primary commodities has exposed Malaysia to tremendous market risk and high unemployment. To reduce the risk inherent in agricultural commodities, the government stepped up industrialisation efforts. The government offered incentives to foreign and local investors for the setting up manufacturing plants in the more technically advanced industries. In addition, trade missions to attract foreign investors were increased.